Diuretic activity of hot flower infusion of nyctanthes arbo-tristis in rats - W.D. Ratnasooriya (Boletín Latinoamericano y del Caribe de Plantas Medicinales y Aromáticas, 2004)
The objective of this study was toevaluate the diuretic potential of Nyctanthus arbotristisLinn. (Oleaceae) flowers using a hot waterinfusion in rats. Different concentrations of theinfusion (3.7, 7.5, 12.5, or 18.7 mg/ kg ), or vehicle,or furosemide (the reference drug at 13 mg/kg), wasorally administered to hydrated rats. Their cumulativeurine output was monitored at hourly intervals for 6hours. The flower infusion induced a significant(P<0.05) diuresis in a dose-related manner. Theonset of this diuretic action was extremely rapid(within 1 hr) and lasted throughout the study period.Further, the flower infusion caused a significantimpairment (P<0.05) of the urinary Na+ and K+ levelsand caused slight but significant (P<0.05)alkalisation. However, it had no significant (P>0.05)effect on urine specific gravity or Na+/K+ ratio of urine.Collectively, these data suggest that the infusioninduces diuresis by basically acting as a potassiumsparing diuretic. It is concluded that these flowershave a promising potential as a safe, effective andcheap diuretic